Assessment of Pregnant Women’s Knowledge and Practices Toward Preterm Labor - Salwa Hazim (Iraqi National Journal of Nursing Specialties, 2023)
Objects To assess the pregnant woman’s knowledge towards preterm labor, and identify the relationship between these women’s knowledge and practices relative to their: Socio-demographic variables. Reproductive variables, previous and present history, socialand psychological factors of pregnant women. Methodology: ٨ descriptive study used an assessment approach in order to assess the knowledge and practices of pregnant women with preterm labor. A purposive sample of (100 ) pregnant women with preterm labor were selected from Al-Alwia maternity teaching hospital , Al-Yarmook teaching hospital , Baghdad teaching hospital, Fatimat AlZahra maternity ع children hospital , Al-Na’aman general hospital, Al-Kadhimia Teaching Hospital and Ibn-Al-Baladi maternity & children hospitals in Baghdad City. The questionnaire consisted of pan (1) which included socio-demographic characteristics previous and present obstetrical history, social and psychological factors, and source of information and part (2) pregnant women knowledge and practices regarding the preterm labor. Reliability and validity of the questionnaire were determined. Data were collected through the use of the questionnaire, the application of the interview technique and review of the pregnant women records. Data were analyzed through descriptive and inferential data approach. Results: The finding of the study shows high mean of scores in women’s knowledge regarding the definition of preterm labor, in sign and symptoms in abdominal pain only, and in warning signs regarding pain like menstrual cramps and uterine contractions, while all remaining items oriented towards low mean of scores. Regarding practices, the results presented high mean of scores in all items regarding pregnant woman’s practices towards preterm labor except in attending the primary health care center (PHCC) and visiting specialist clinic in bleeding , nausea , vomiting and leaking liquor . ٠ Healthy Directorate of Baghdad/ Karkh/ Al-١’amtook Secondary Midwifery/ ministry of Health ٠٠ Maternity Nursing Department /College of Nursing / University of Baghdad Knowledge and Practices Toward Preterm Labor The finding of the study also presented a significant association between preterm labor and women’s occupation, abortion occurrence, still birth and social factors in items of overload housework, family conflicts, and presence of sad and happy events, psychological fears, including the fear of not having partner support, fear of daily housework, fear of weak ability to cover their personal needs and source of information. The pregnant women’s practices regarding the preterm labor had a significant association with women’s socioeconomic status, abortion occurrence, delivery of abnormal fetus, and order of pregnancy. Also there is an association between the practices and the social factors concerning absence of partner support. Regarding the psychological fears there was a significant association presented in the expecting of troubles during pregnancy. Recommendation: The study recommended that health education program can be designed and constructed for pregnant women toward preterm labor to promote their knowledge and practices to assume an optimal level of self-management within the parameters of their problem.